Dietary behaviour and physical activity policies in Europe: learnings from the Policy Evaluation Network (PEN). (29th November 2022) - Ahrens, Wolfgang; Brenner, Hermann; Flechtner-Mors, Marion; Harrington, Janas M; Hebestreit, Antje; Kamphuis, Carlijn B M; Kelly, Liam; Laxy, Michael; Luszczynska, Aleksandra; Mazzocchi, Mario; Murrin, Celine; Poelman, Maartje P; et al.
Abstract: The European Policy Evaluation Network (PEN), initiated in autumn 2018, aimed at advancing the evidence base for public policies impacting dietary behaviour, physical activity and sedentary behaviours in Europe. This is needed because non-communicable diseases—the leading cause of global mortality—are substantially caused by physical inactivity and unhealthy dietary behaviours, which in turn are driven by upstream factors that have not yet been addressed effectively by prevention approaches. Thus, successful policy interventions are required that target entire populations and tackle the 'causes of the causes'. To advance our knowledge on the effective implementation of policies and their impact in terms of improving health behaviours, PEN focused on five research tasks: (i) Adaptation and implementation of a Food Environment Policy Index (Food-EPI) and development of a Physical Activity Environment Policy Index (PA-EPI); (ii) Mapping of health-related indicators needed for policy evaluation and facilitating a harmonized pan-European approach for surveillance to assess the impact of policy interventions; (iii) Refining quantitative methods to evaluate the impact of public policies; (iv) Identifying key barriers and facilitators of implementation of policies; and (v) Advance understanding the equity impact of the development, implementation and evaluation of policies aimed at promoting physical activity and a healthy diet. Finally, and in order to provide concrete evidence for policymaking, existing exemplary policies, namely sugar-sweetened beverages taxation, active transport policies and school policies on nutrition and physical activity were assessed in consideration of these five tasks. At the end of the PEN project's formal runtime, considerable advancements have been made. Here, we present an overview of the most important learnings and outputs.